The effectiveness of metacognitive therapy on experiential avoidance, uncertainty intolerance and positive metacognitive beliefs in women with obsessive-compulsive disorder - Yadollahi Ardestani, Shirin; Keykhosrovani, Moloud; Amini, Naser (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The purpose of this research was the effectiveness of metacognitive therapy on experiential avoidance, uncertainty intolerance and positive metacognitive beliefs in women with obsessive-compulsive disorder. Methods: The current research method is semi-experimental and the design used in this research is a pre-test-post-test design with a control group and a follow-up period. The statistical population of the research was all women suffering from obsessive-compulsive disorder who referred to counseling and psychotherapy centers in Tehran in the months of February and March of 2021. The research sample included 30 women with obsessive-compulsive disorder who referred to counseling and psychotherapy centers in Tehran between February and March of 1400. Data were collected using the Yale-Brown Obsessive Compulsive Questionnaire (1989), the Experiential Avoidance Questionnaire by Bond et al. (2011), the Intolerance of Uncertainty Questionnaire by Friston et al. Obtained. In this research, the protocol of Wells (2000) was used to perform metacognitive therapy, which was performed once a week for 8 sessions of 90 minutes on the experimental group. The data was analyzed using the method of analysis of variance with repeated measurements and SPSS software. Results: The findings showed that metacognitive therapy on experiential avoidance (F=13.53, P